The Role of TVET in Mitigating Climate Change among SMEs (Journal of Geography, Meteorology and Environment, 2022)
Business enterprises, particularly small and medium scale enterprises (SMEs) are the mainstay of many economies, but are faced with a lot of challenges, including climate change impacts.This work investigated the role of TVET in mitigating climate change among SMEs. Questionnaire survey was conducted on 210 SMEs randomly selected in the three economic hubs: Awka, Onitsha and Nnewi in southeast Nigeria. Results showed that the level of awareness on climate change was low and that even though businesses contribute to it, they were mostly not aware of that. Much of the SMEs use sources of power that is less climate friendly (generators) than other more environmentally friendly options (mainly solar energy).The SMEs have requisite knowledge about their businesses but their level of awareness on TVET and adaptive capacity to climate change are low. Their levels of education did not determine or influence their knowledge on TVET; hence the need to expose firms and the society to its rudiments. Formal education was perceived as a better method of teaching TVET, but needs to be combined with informal education so that much of the staff of SMEs could be reached more effectively. Transfer of information on green industrialization was deemed necessary and methods such as: using experienced entrepreneurs,seminars/workshops, annual training, government enforced training and short courses/internships (in decreasing order of effectiveness) were identified as veritable pathways to achieving that. There is need to sensitize the SMEs to have plans for managing climate risks and promote the use of technologies that are not only recent, but are climate friendly and green. TVET has the capacity to actualize the desired green industrialization and climate change adaptations among SMEs, but will require proactive measures such as promoting new forms of education for employees, ongoing training within companies, establishing vocational centres and exposing the younger generation to such initiatives all through their formal education process.
Keywords: climate change; economy; environment; greening; TVET